Development affordable ferrocement roof cover using sustainable building material - Umar, Hj. Kassim; Wan Mohd Sabki, Wan Omar; Kamarudin, Mohd Nor (Real Estate and Housing Developers' Association (REHDA), Federal Territories, 2011)
World Class Sustainable Cities 2009 (WCSC 2009) organized by Real Estate and Housing Developers' Association (REHDA), Federal Territories, Malaysian Institute of Planners (MIP) and Malaysian Institute of Architects (PAM), 24th March 2009 at Renaissance Hotel, Kuala Lumpur, Malaysia.